2022
DOI: 10.1111/jerd.12967
|View full text |Cite
|
Sign up to set email alerts
|

Single‐rooted extraction socket classification: A systematic review and proposal of a new classification system based on morphologic and patient‐related factors

Abstract: Taxonomy and classification of a disease contributes to facilitating the diagnosis and treatment planning process and simplifies communication between clinicians. The aim of this study was to provide a critical appraisal based on a systematic review of the single-rooted extraction socket (ES) classifications and subsequently, introduce a new classification system combining the cornerstones of the previously proposed systems and based on the latest consensus in implant dentistry. Following the systematic search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
(185 reference statements)
0
8
0
Order By: Relevance
“…While the included studies described the general condition of the extraction socket, crucial in-situ site characteristics pertaining to the soft tissue (such as phenotype, level or loss, quality, and blood supply) and/or hard tissue (including buccal bone thickness or dehiscence, defect walls, apical topography, and root position) were not reported. 51 Furthermore, this systematic review did not consider outcomes such as implant survival, patient-reported outcome measures, incidence of peri-implant diseases, costs, and esthetics, despite their potential influence on decision-making. 52 Finally, it is important to note that the evaluation of bone reconstructions in severely resorbed sockets fell beyond the scope of the present review.…”
Section: Discussionmentioning
confidence: 99%
“…While the included studies described the general condition of the extraction socket, crucial in-situ site characteristics pertaining to the soft tissue (such as phenotype, level or loss, quality, and blood supply) and/or hard tissue (including buccal bone thickness or dehiscence, defect walls, apical topography, and root position) were not reported. 51 Furthermore, this systematic review did not consider outcomes such as implant survival, patient-reported outcome measures, incidence of peri-implant diseases, costs, and esthetics, despite their potential influence on decision-making. 52 Finally, it is important to note that the evaluation of bone reconstructions in severely resorbed sockets fell beyond the scope of the present review.…”
Section: Discussionmentioning
confidence: 99%
“…The rehabilitation of an extremely atrophic maxilla is difficult for dentists because of insufficient bone that precludes placement of conventional‐length dental implants 1 . After tooth extraction, alveolar bone resorption is usually inevitable, and may compromise implant placement 2 . Various bone augmentation procedures have been suggested which increase the bone level and allow rehabilitation with implant‐supported prostheses in cases of atrophic maxilla.…”
Section: Introductionmentioning
confidence: 99%
“…1 After tooth extraction, alveolar bone resorption is usually inevitable, and may compromise implant placement. 2 Various bone augmentation procedures have been suggested which increase the bone level and allow rehabilitation with implant-supported prostheses in cases of atrophic maxilla. These include grafting procedures, apposition graft with or without Le Fort I osteotomy, and sinus lift.…”
Section: Introductionmentioning
confidence: 99%
“…9 Many authors classified the alveolar sockets according to the characteristics of both hard and soft tissues [10][11][12][13] and to patient-related factors. 14 The aim of the bone graft is to acts like a scaffold to promote bone formation and to maintain the ridge volume stable during the healing period. 6,15 Therefore, ARP procedures can be considered a treatment to minimize dimensional bone changes, which physiologically occurs after tooth extraction, 3,8 and to facilitate the following implant insertion.…”
Section: Introductionmentioning
confidence: 99%
“…After a tooth extraction performed in the least traumatic way, the alveolar socket is grafted with a bone substitute with or without a membrane 9 . Many authors classified the alveolar sockets according to the characteristics of both hard and soft tissues 10–13 and to patient‐related factors 14 …”
Section: Introductionmentioning
confidence: 99%